Analisis Efektivitas Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Organisasi pada Perusahaan X - Ading Rahman Sukmara (EBISMAN eBisnis Manajemen, 2026)
This study aims to analyze the effectiveness of human resource management at Company X in improving organizational performance. Human resources are a strategic factor that plays an important role in supporting the operational success of a company. This research uses a descriptive approach with qualitative methods supported by simple quantitative data analysis. Data were collected through interviews, observations, and documentation related to workforce management within the company. The results indicate that the number of employees has increased along with the development of the company's operational activities. The workforce structure is dominated by productive-age employees who have good adaptability to technological developments and work demands. However, several challenges were identified in human resource management, particularly in workforce planning, recruitment processes, and the effectiveness of training and employee performance evaluation programs. Therefore, the company needs to improve its human resource management system through more selective recruitment processes, relevant training programs, and a more objective performance evaluation system. These improvements are expected to enhance employee productivity and strengthen the company's competitiveness.